Application of ecological attributes in the contemporary landscape assessment research - Othman, Jamilah; Abdullah, Muhammad Faris; Ahmad Sarkawi, Azila; Abdullah, Fadzidah; Ahmad Kamaruddin, NurEmira (University of Lagos, 2016)
Ecological attributes are most commonly associated to nature-based landscape assessment. But their applications are less discussed in the non-nature based landscape assessment. This paper reviews a collection of 31 journal articles, which were published between 1974 and 2015. The results show that ecological attributes such as water, vegetation and landform, have increasingly featured in various studies on non-nature based landscape assessment studies. This suggests that ecological attributes can support and enhance the assessment of both natureand non-nature-based landscapes significantly. To this end, this paper also proposes a preliminary ecological model for landscape assessment research.